Exploring the interplay of soft power, culture, and cinema on a global scale: a review of current research and future directions - Yishan, Liu; Kasimon, Diyana; Chwee Fang, Ng (Natural Sciences Publishing, 2023)
This paper examines the significance of soft power in academia, policy-making, and international relations. It reviews the current state of soft power research, identifies gaps in the literature, and explores the interplay of soft power, culture, and cinema. The paper analyses the research hotspots in Chinese soft power research and highlights the need for further research to enhance soft power strategies on a global scale.